Backscatter-difference Measurements of Cancellous Bone Using an Ultrasonic Imaging System. (July 2016) - Hoffmeister, Brent K.; Smathers, Morgan R.; Miller, Catherine J.; McPherson, Joseph A.; Thurston, Cameron R.; Spinolo, P. Luke; Lee, Sang-Rok
Backscatter-difference measurements may be used to detect changes in bone caused by osteoporosis. The backscatter-difference technique measures the power difference between two portions of an ultrasonic backscatter signal. The goal of this study is to evaluate the feasibility of using an ultrasonic imaging system to perform backscatter-difference measurements of bone. Ultrasonic images and backscatter signals were acquired from 24 specimens of human cancellous bone. The signals were analyzed in the frequency domain to determine the normalized mean backscatter-difference (nMBD) and in the time domain to determine the normalized backscatter amplitude ratio (nBAR). The images were analyzed to determine the normalized pixel value difference (nPVD), which measures the difference in average pixel brightness between regions of interest placed at two different depths in the image. All three parameters were found to increase with bone mineral density. The signal-based parameters, nMBD and nBAR, correlated well with bone mineral density, yielding linear correlation coefficients that ranged from 0.74 to 0.87. The image based parameter, nPVD, performed somewhat less well, yielding correlation coefficients that ranged from 0.42 to 0.81. These results suggest that ultrasonic imaging systems may be used to perform backscatter-difference measurements for the purpose of ultrasonic bone assessment.